Local Challenges and Opportunities for Language and Literacy Researchers and Educators - Landis, David (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper presents a three dimensional array of contemporary challenges and opportunities for language and literacy researchers and educators. The challenges and opportunities result from dynamic human migration, widespread use of mobile digital technology, and the development of the internet. Recent publications are discussed that exemplify the challenges and opportunities. Particular attention is given to spaces as local contexts for language and literacy learning. Focusing discussion upon the challenges and opportunities is one way of building knowledge about how people use modes of communication to develop, use, and learn language and literacies.